Performance of Public Procurement: Recent National Literature Review and the Proposition of a Research Agenda (Gestão & Regionalidade, 2021)
This study sought to investigate how Brazilian literature has examined the performance of using public procurement to implement public policies in Brazil, by mapping the state of the art in an revision of the literature for the decade 2007-2017. The relevance of this research resides in the presentation of the national panorama of research concerning the performance of government procurement, thus contributing to the Public Administration literature and to the debate on evaluation of the use of public procurement. Three thematic categories summarize the literature: Outputs of the use; The use of multicriteria models on measuring the performance, and; The use of the State's procurement power. A research agenda presents two gaps: studies that test the performance of public procurement under a compared and multicriteria perspective, and; studies that test theoretical variables that are characteristic to the use of public procurement, such as user satisfaction, transparency or accountability.Keywords: public procurement; performance in the public sector; the use of the State's procurement power.
Keywords: public procurement; performance in the public sector; the use of the State's procurement power